EDUKASI KESELAMATAN DAN KESEHATAN KERJA KEPADA SISWA SMK FARMASI - Iva Mindhayani; Intan Permatasari; Alfin Orlando Zulfan (Universitas PGRI Yogyakarta, 2026)
The risk of workplace accidents can happen to anyone, anytime, anywhere and certainly not expected to happen. The risk of accidents can also occur in schools such as at SMK SMF INDONESIA Yogyakarta. There is interaction between students and teachers in carrying out activities both in the classroom, outside the classroom, and also in the laboratory. Accidents and diseases caused by work activities can be avoided as early as possible if all elements of the school understand the risks and hazards that can occur in the school environment. The implementation of school OSH and its understanding of students and teachers is still lacking. Most of them only have general knowledge of OSH without being given other essential understandings. Awareness of OSH culture is a powerful way to prevent work accidents. The implementation of OSH is the joint responsibility of all parties involved. OHS education must continue to be carried out as an effort to instil an OHS culture. Thus, they have a mindset of working or doing things correctly by always being careful and vigilant about potential hazards around them. Based on these problems, K3 education was conducted for students of SMK SMF INDONESIA Yogyakarta class XII. The method used in the abdimas activity is counselling. Pengabdi presented material related to the application of K3 in schools. As a result of this activity, the participants increased their knowledge about K3. Keyword: Hazards, OHS Culture, Education, Pharmacy, Students